Pediatric dental care in patients with down syndrome: A literature review - Uchôa, Sue Ann Castro Lavareda; Corrêa, Suelen Castro Lavareda; Corrêa, Davi Lavareda; Corrêa, Vânia Castro (Seven Editora, 2024)
Down syndrome (DS) is a genetic condition caused by trisomy 21, and is the most prevalent congenital mental anomaly. This syndrome encompasses a wide variety of mental, behavioral, and physical changes, including oral modifications that require specialized attention from dentists. Dental treatment for patients with Down Syndrome seeks to eliminate or control the specific difficulties these individuals face, highlighting the importance of an early approach to provide the best possible outcomes. This study aims to conduct a literature review of behavioral management techniques in pediatric dental care for children with Down syndrome. There is a need for the dental surgeon to adopt a specific conduct during the dental treatment of these patients, considering their particularities. The controversy among the authors regarding the rate of caries lesions in patients with Down syndrome highlights the complexity of this issue. The study also highlights the importance of family involvement throughout dental treatment and emphasizes the need for dental surgeons to be prepared to deal with the various characteristics and individual needs of each child with Down syndrome. In summary, the research highlights the relevance of a holistic and individualized approach to ensure the quality of dental care for these patients. DOI: https://doi.org/10.56238/sevened2023.007-041